2012
DOI: 10.1002/cbic.201100710
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptable Luminescence Resonance Energy Transfer Assay for Measuring and Screening Protein–Protein Interactions and their Inhibition.

Abstract: Protein–protein interactions (PPIs) are central to biological processes and represent an important class of therapeutic targets. Here we show that the interaction between FK506 binding protein 12 fused to green fluorescent protein (GFP-FKBP) and the rapamycin-binding domain of mTor fused to Escherichia coli dihydrofolate reductase (FRB-eDHFR) can be sensitively detected (signal-to-background (S:B) >100) and accurately quantified within an impure cell lysate matrix using a luminescence resonance energy transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Another important component of the sensor design is the eDHFR domain that binds to TMP-linked small molecules with high affinity ( K D , ∼1 nM) and selectivity ( Miller et al., 2005 ). In our prior work, we have shown that TMP-coupled Tb(III) complexes bind effectively to eDHFR fusion proteins in vitro ( Rajapakse et al., 2009 ), in lysates ( Yapici et al., 2012 ) and in living mammalian cells ( Rajapakse et al., 2010 ). Given the high affinities of TMP for eDHFR and of commonly used chelators for Tb(III) ( K A > 10 14 M −1 ) ( Selvin, 1996 ), assemblies of eDHFR and TMP-Tb(III) remain stable in cells or at high dilution in challenging environments.…”
Section: Resultsmentioning
confidence: 99%
“…Another important component of the sensor design is the eDHFR domain that binds to TMP-linked small molecules with high affinity ( K D , ∼1 nM) and selectivity ( Miller et al., 2005 ). In our prior work, we have shown that TMP-coupled Tb(III) complexes bind effectively to eDHFR fusion proteins in vitro ( Rajapakse et al., 2009 ), in lysates ( Yapici et al., 2012 ) and in living mammalian cells ( Rajapakse et al., 2010 ). Given the high affinities of TMP for eDHFR and of commonly used chelators for Tb(III) ( K A > 10 14 M −1 ) ( Selvin, 1996 ), assemblies of eDHFR and TMP-Tb(III) remain stable in cells or at high dilution in challenging environments.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro assay performed in 96-well plates, we titrated a fusion of GFP to FK506 binding protein 12 (GFP–FKBP12) against a fixed concentration of eDHFR fused to the rapamycin binding domain of mTOR (FRB–eDHFR). Following the addition of rapamycin (to induce protein interaction) and the TMP-Tb(III) complex 7 , we observed a ∼3500% increase in the long-lifetime, Tb-to-GFP-sensitized emission . The high dynamic range of Tb(III)-based FRET (>30-fold) greatly exceeds the best dynamic range for nondimerizing fluorescent proteins (<5-fold) observed in vitro and hints at the potential sensitivity of lanthanide-based FRET microscopy. , …”
Section: Protein-targeted Lanthanide Complexesmentioning
confidence: 78%
“…The rapamycin-induced interaction between FKBP12 and FRB , presents an ideal model system for quantifying the detection limit, SNR, dynamic range, and other measures of the image quality that may be observed with time-gated FRET imaging of protein–protein interactions. Because both proteins diffuse throughout the cytoplasm and nucleus when expressed in mammalian cells, cytoplasmic signal levels are proportional to the total cellular protein concentration.…”
Section: Quantitative Time-gated Microscopy With Lanthanidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spurred by our interest in developing luminescent lanthanide complexes for bioanalytical and imaging applications, 10,11,6063 we sought to develop more efficient strategies for preparing Cy-TTHA ( 6 ) and Cy-DTPA ( 11 ) derivatives. Herein, we report a modular, five-step syntheses of Cy-TTHA ( 6 ) and Cy-DTPA ( 11 ) with good overall yields.…”
mentioning
confidence: 99%